Assessing Policies for the Uptake of Sustainable Aviation Fuels Using the Impact Monitor Framework - Inge Mayeres; Emanuela Peduzzi; Marko Alder; Fabian Baier; Kuno Buchtal; Sreyoshi Chatterjee; Maximilian Clococeanu; David Ennen; Marc Gelhausen; Alf Junior; Alexandra Leipold; Prajwal Shiva Prakasha; et al. (Engineering Proceedings, 2025)
The Impact Monitor Project, funded by the EU, aims to develop an impact assessment framework for European aviation. This paper uses the framework for the modelling and simulation of an impact assessment at the air transport system level, focusing on policies for the uptake of sustainable aviation fuels. It aims to demonstrate the capabilities developed by the Impact Monitor framework and its interactive dashboard application at the air transport system level.